A new species of Saxofridericia subgenus Acrotheca (Rapateaceae) from Amazonas State, Brazil - Berry, Paul E.; Krahl, Amauri Herbert (Phytotaxa, 2017)
Saxofridericia brasiliensis P.E.Berry & Krahl, a new species of Saxofridericia subgenus Acrotheca, is described and illustrated. It is most closely related to Saxofridericia aculeata Körnicke, but differs in its entire-margined leaves and narrower leaf blades. It is so far known only from white-sand campina vegetation north of Manaus along the Caracaraí highway in Amazonas State, Brazil.